Characterization of the IncX3 Plasmid Producing blaNDM–7 From Klebsiella pneumoniae ST34 - Chen, Qiong; Zhou, Jiawei; Wu, Shenghai; Yang, Yunxing; Yu, Daojun; Wang, Xianjun; Wu, Min (Frontiers in Microbiology, 2020)
Carbapenemase-producing Klebsiella pneumoniae has been a major clinical threat worldwide because therapeutic options are limited. Although New Delhi metallo-β-lactamase (NDM) is an important carbapenemase responsible for carbapenem resistance, it is uncommon in carbapenemase-producing K. pneumoniae in China. In this study, we described strain HZW25, an NDM-7-producing K. pneumoniae strain belonging to sequence type 34 (ST34). HZW25 exhibited resistance to all β-lactams tested but was susceptible to aminoglycosides and fluoroquinolones. The whole genome of HZW25 was sequenced with Pacific Biosciences RSII SMRT technology. HZW25 was composed of one chromosomal DNA and four plasmids, and the resistance genes of HZW25 were all located on the chromosome, except blaNDM-7 was located on a conjugative plasmid belonging to type IncX3 designated P4. The results of conjugation and transformation experiments showed that blaNDM-7 could be horizontally transferred successfully from the donor strain, HZW25, to the recipient strains, E. coli J53 and E. coli DH5α. The NDM variant transposable elements of the blaNDM-7-harboring plasmid P4 were the ISL3 and IS3000 families. The upstream region of blaNDM-7 contained ΔISAba125, which was inserted near the IS5 or ΔIS5 sequence. Our study is the first report of metallo-β-lactamase NDM-7 in a carbapenemase-producing K. pneumoniae strain with ST34 in China. The emergence of NDM-producing K. pneumoniae would be troublesome during treatment using ceftazidime-avibactam. Therefore, the rapid and accurate identification of carbapenemase-producing K. pneumoniae is necessary.